How Different Parental Leave Schemes Create Different Take-Up Patterns: Denmark in Nordic Comparison - Rostgaard, Tine (2021)
The prevailing gender ideologies in the Nordic countries generally support the equal division of work and family life between men and women, including the equal sharing of parental leave. Regardless, as the exceptional case in the Nordic region, Denmark currently has no father’s quota, and this despite the strong impact such policy has effectively proven to have on gender equality in take-up of parental leave. While a quota intended for the father is instead implemented in Denmark via collective agreements, this is mainly available for fathers in more secure labour market positions. This situates Danish fathers, mothers and their children very unequally regarding parental leave entitlements, and the existing inequalities continue across gender, social class and labour market positions. This article explores to what extent institutional variables vis-à-vis cultural explanations such as gender attitudes provide an understanding of why Danish fathers take less parental leave than other Nordic fathers. We use data from the European Values Study (1990‒2017) as well as administrative data for fathers’ parental leave take-up in the same period, relative to the other Nordics and for specific education backgrounds. We conclude that Danish men and women are even more supportive of gender equality in terms of work‒family life sharing compared to other Nordic countries. This indicates that institutional conditions such as parental leave entitlement matter for leave take-up, but in the Danish case attitudes do less so. Not having a father’s quota seems to affect fathers disproportionally across the education divide, and the lower parental leave take-up among Danish men with little education is primarily ascribed to their labour market insecurity. The policy implication is clear: If we want mothers and fathers with different social backgrounds to share parental leave more equally, the policy must change—not attitudes.